Pengaruh Kinerja Keuangan dan Ukuran Perusahaan Terhadap Nilai Perusahaan Transportasi dan Logistik Yang Terdaftar Di BEI (2021-2023) - Callista, Enjelly Talitha; Yuliati, Anik (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to examine the effect of Financial Performance profitability (ROA), liquidity (CR), and leverage (DER) as well as Company Size (SIZE) on firm value (PBV) in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. This type of research is quantitative method research. The data used is secondary data in the form of the company’s annual financial statements obtained from the official website of the Indonesia Stock Exchange. The population used in this study are all transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The sampling technique in this study was purposive sampling method, so that 28 companies that met the criteria were obtained, and the observation sample period used was 3 years. The data analysis technique used is multiple linear regression analysis with the SPSS 30 program. The results showed that 1) Financial Performance Profitability (ROA) has no effect on firm value. 2) Liquidity Financial Performance (CR) has no effect on firm value. 3) Solvency Financial Performance (DER) has an effect on firm value. 4) Company Size (SIZE) has no effect on firm value.